PENGALIHAN HAK ATAS TANAH UNTUK KEPENTINGAN UMUM MENURUT HUKUM ISLAM - Latif, Faozi; Sunarko, Asep (Ahkam: Jurnal Hukum Islam, 2020)
Transfer of land rights for public interest in the community often occurs. The transfer of land is done for various purposes, including the construction of roads, hospitals, places of education, places of worship and others. This research is pursued in the discussion of the process of transferring land rights in the public interest according to Islamic law and the consequences for the transfer of ownership rights to land in the public interest. This research uses library research. The results of the study explained that in Islamic law the transfer of land rights was carried out in the time of the Prophet and also shahaba. Transfer of land rights for public interest in Islam can be done through buying and selling or compensation and endowments. After the transfer of land rights, the rights to manage and use the land are transferred to the second party. Keywords: Land, Public Interests, Waqf.